The Lymph Self-Antigen Repertoire - Santambrogio, Laura; Clement, Cristina (Frontiers in Immunology, 2013)
The lymphatic fluid originates from the interstitial fluid which bathes every parenchymal organ and reflects the “omic” composition of the tissue from which it originates in its physiological or pathological signature. Several recent proteomic analyses have mapped the proteome-degradome and peptidome of this immunologically relevant fluid pointing to the lymph as an important source of tissue-derived self-antigens. A vast array of lymph-circulating peptides have been mapped deriving from a variety of processing pathways including caspases, cathepsins, MMPs, ADAMs, kallikreins, calpains and granzymes, among others. These self peptides can be directly loaded on circulatory dendritic cells and expand the self-antigenic repertoire available for central and peripheral tolerance.